The Influence of Social Media Influencer, Perceive Price, and Sales Promotion on Purchase Intention - Rohman, Fatchur; Tambunan, Joseph Dolok Hidefumi (Jurnal Entrepreneur dan Entrepreneurship, 2024)
Fashion products currently face very tight competition, especially in Indonesia. Prospective buyers will consider certain factors before making a purchase. Therefore, manufacturers must be smart to survive today's competitive business environment. This research aims to identify the effects of social media influencers, perceived price, and sales promotion on the intention of people in the Special Capital Region of Jakarta to purchase Erigo products. The method used is a quantitative explanatory study that clarifies the causal relationship among related variables. Using a purposive sampling technique, 170 Erigo consumers living in Jakarta's Special Capital Region were selected as respondents. Data analysis was performed using multiple regression. The results indicated that social media influencers, perceived price, and sales promotions each positively and significantly impact the intention to buy Erigo products. It is also shown that local products are not inferior to similar products if producers focus on social media influencers, perceived price, and sales promotion.